Recent Observations in Surface Electromyography Recording of Triceps Brachii Muscle in Patients and Athletes - Md. Asraf Ali; Kenneth Sundaraj; R. Badlishah Ahmad; Nizam Uddin Ahamed; Md. Anamul Islam (Applied Bionics and Biomechanics)
Objective: To observe and analyse the literature on the use of surface electromyography electrodes, including the shape, size, and metal composition of the electrodes used, the interelectrode distance, and the anatomical locations on the muscle at which the electrodes are placed, for the observation of the triceps brachii muscle activity in patients and athletes.